THE EFFECT OF GENRE BASED APPROACH ON STUDENTS’ WRITING ABILITY OF RECOUNT TEXT - Dina Maryana Mastura; Safnil Arsyad; Irwan Koto (Universitas Bengkulu, 2020)
The objective of this research was to investigate the effect of genre based approach on students’ writing ability of recount text. This study was conducted through quasi experimental design. The population were the total of 52 second year students of SMAN 05 Bengkulu Tengah (IPS1 as experimental class dan IPS2 as control class). Theexperimental class was taught by using genre based approach and the control class was taught by using the conventional approach.The instrument was a written test of a recount text. Before analyzing the data by using t-test, a normality and homogenity test were conducted, then scored by using assessment rubric of Heaton (1988). The result showed that there was significant effect of genre based approach on students’ writing ability of recount text. The effects were on the content, organization, vocabulary, language use, and mechanics.